La tradizione drammatico-performativa della cultura náhuatl nel teatro di evangelizzazione francescano - Sara Poledrelli (Confluenze, 2016)
The research follows, on one hand the evolutionary stages of evangelization theatre, on the other, traces a panorama of the different existing performative styles in pre-Hispanic times, to detect which elements of the para- dramatic indigenous rituals and protocols survived in religious theatre set up by Franciscans in the American-hispanic ground. We want to underline how the contents and the forms are the result of miscegenation and syncretism, that were folklorized after the fall of the missionary theatre, and crystallized into a popular dramatic repertoire which exhibits strong survivals of native culture, sometimes only subtly hidden under the Christian and European appearance.